Could a Shigella vaccine impact long-term health outcomes?: Summary report of an expert meeting to inform a Shigella vaccine public health value proposition, March 24 and 29, 2021. (December 2022) - Bagamian, Karoun H.; Puett, Chloe; Anderson, John D.; Muhib, Farzana; Pecenka, Clint; Behrman, Jere; Breiman, Robert F.; Edoka, Ijeoma; Horton, Susan; Kang, Gagandeep; Kotloff, Karen L.; Lanata, Claudio F.; et al.
Abstract: Shigellosis is a leading cause of diarrhea and dysentery in young children from low to middle-income countries and adults experiencing traveler's diarrhea worldwide. In addition to acute illness, infection by Shigella bacteria is associated with stunted growth among children, which has been linked to detrimental long-term health, developmental, and economic outcomes. On March 24 and 29, 2021, PATH convened an expert panel to discuss the potential impact of Shigella vaccines on these long-term outcomes. Based on current empirical evidence, this discussion focused on whether Shigella vaccines could potentially alleviate the long-term burden associated with Shigella infections. Also, the experts provided recommendations about how to best model the burden, health and vaccine impact, and economic consequences of Shigella infections. This international multidisciplinary panel included 13 scientists, physicians, and economists from multiple relevant specialties. According to the panel, while the relationship between Shigella infections and childhood growth deficits is complex, this relationship likely exists. Vaccine probe studies are the crucial next step to determine whether vaccination could ameliorate Shigella infection - related long-term impacts. Infants should be vaccinated during their first year of life to maximize their protection from severe acute health outcomes and ideally reduce stunting risk and subsequent negative long-term developmental and health impacts. With vaccine schedule crowding, targeted or combination vaccination approaches would likely increase vaccine uptake in high-burden areas. Shigella impact and economic assessment models should include a wider range of linear growth outcomes. Also, these models should produce a spectrum of results—ones addressing immediate benefits for usual health care decision-makers and others that include broader health impacts, providing a more comprehensive picture of vaccination benefits. While many of the underlying mechanisms of this relationship need better characterization, the remaining gaps can be best addressed by collecting data post-vaccine introduction or through large trials.